PENGARUH HUMBLE LEADERSHIP DAN PROFESIONALISME TERHADAP KINERJA KARYAWAN TERHADAP PERUSAHAAN UKM EXPRESS KEDIRI - Ulfatun Nuril Kamidah; BambangSuwarsono; Ahmad Jauhari (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research aims to analyze the influence of humble leadership and professionalism on employee performance. The research method used is quantitative with a survey approach, where data is collected through questionnaires distributed to employees at the UKM Express company. Data analysis was carried out using SPSS software. The results of the regression analysis show that humble Leadership has a positive and significant influence on employee performance with values. The regression coefficient is 0.45 and significance is 0.003 (p < 0.05). Professionalism also has positive and significant influence on employee performance with the regression coefficient value equal to 0.50 and significance 0.001 (p < 0.05). Together, humble leadership and professionalism explains 60% of the variability in employee performance (R² = 0.60), shows that the combination of these two variables is a strong predictor of employee performance. The implication of this research is the importance of companies to apply humble leadership and increase professionalism to achieve performance optimal employees.